2014
DOI: 10.3892/ijo.2014.2733
|View full text |Cite
|
Sign up to set email alerts
|

Long-term exposure to gefitinib induces acquired resistance through DNA methylation changes in the EGFR-mutant PC9 lung cancer cell line

Abstract: Abstract. this study was designed to identify epigenetically regulated genes and to clarify the contribution of epigenetic alteration to acquired resistance to epidermal growth factor receptor-tyrosine kinase inhibitors (egfr-tKis). We established a gefitinib-resistant lung cancer cell line, PC9, which was originally gefitinib-sensitive, by serial long-term exposure to gefitinib. RNA and DNA were collected from both gefitinib-sensitive and -resistant PC9 cells, and comprehensive DNA methylation and mRNA expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…We compared the differentially expressed mRNAs with other studies, and the high consistency strongly supported our predictions. For example, in the mRNA expression analysis using Agilent SurePrint G3 Human Gene Expression 8x60K array of a gefitinib-resistant lung cancer cell line (19), IGFBP3 was found to be expressed differentially, which is in accordance with our results. Additionally, the constitutive activation of EGFR tyrosine kinase receptor caused by mutation and/or amplification is closely correlated with the development, progression and poor prognosis of NSCLC, through the activation of various downstream signaling pathways.…”
Section: Discussionsupporting
confidence: 90%
“…We compared the differentially expressed mRNAs with other studies, and the high consistency strongly supported our predictions. For example, in the mRNA expression analysis using Agilent SurePrint G3 Human Gene Expression 8x60K array of a gefitinib-resistant lung cancer cell line (19), IGFBP3 was found to be expressed differentially, which is in accordance with our results. Additionally, the constitutive activation of EGFR tyrosine kinase receptor caused by mutation and/or amplification is closely correlated with the development, progression and poor prognosis of NSCLC, through the activation of various downstream signaling pathways.…”
Section: Discussionsupporting
confidence: 90%
“…Two previous studies were identified that had used mRNA microarray analysis to examine changes of gene expression in lung cancer cells with acquired resistance to either gefitinib or erlotinib (12,31). However, these studies only examined one cell line resistant to either gefitinib or erlotinib.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that high level of IGFBP3 is a protective factor and is associated with good prognosis in patients with advanced NSCLC (13)(14)(15). No cases of IGFBP3 gene deletion in humans have been reported, but hypermethylation of the IGFBP3 promoter is involved in loss of IGFBP3 expression in NSCLC, and may be related to the development of acquired treatment resistance (16)(17)(18)(19). Although a prior report has shown that heterozygously deleted Igfbp3 transgenic mice with mutant IGF1 expression have higher lung tumorigenesis, there was no increased tumorigenesis in homozygously deleted Igfbp3 mice compared with wild-type Igfbp3 control, which was unexplained (20).…”
Section: Introductionmentioning
confidence: 99%